Transparansi Material Information bagi Pemegang Saham Minoritas dalam Proses Merger dan Akuisisi: Studi Perbandingan Regulasi Good Corporate Governance Indonesia dan Singapura - Catharina Crisanty Eva Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study compares the Good Corporate Governance (GCG) regulations concerning the transparency of material information for minority shareholders during Mergers and Acquisitions (MA) in Indonesia (UUPT POJK) and Singapore (The Takeover Code CA). The study analyzes disclosure obligations to prevent asymmetric information and the role of Directors' fiduciary duty.It was found that although disclosure obligations in both countries are protective, Singapore is superior in preventing asymmetric information through its principle-based approach which strictly enforces the principle of Equality of Information (Rule 12 The Takeover Code) , prohibiting selective disclosure. Conversely, Indonesia has significant gaps due to reliance on formal materiality thresholds and a lack of universal detailed standards ,thus keeping the risk of asymmetric information high.Regarding Directors' fiduciary duty, this obligation serves as the main catalyst. In Indonesia (Pasal 97 UUPT), the focus is on the Duty of Care and Duty of Loyalty in ensuring document integrity, while in Singapore (Section 157 CA), the focus is directed towards enforcing the principle of equal treatment (General Principle 1). Procedurally, Indonesia excels in granting an explicit legal Exit Right (Pasal 62 UUPT) for dissenting minorities, whereas Singapore emphasizes price guarantee through the Mandatory Offer (Rule 9 The Takeover Code).